AAGBI guidelines: the use of blood components and their alternatives 2016. (8th April 2016) - Klein, A. A.; Arnold, P.; Bingham, R. M.; Brohi, K.; Clark, R.; Collis, R.; Gill, R.; McSporran, W.; Moor, P.; Rao Baikady, R.; Richards, T.; Shinde, S.; et al.
Summary: Blood transfusion can be life‐saving. Anaesthetists regularly request and administer blood components to their patients. All anaesthetists must be familiar with indications and appropriate use of blood and blood components and their alternatives, but close liaison with haematology specialists and their local blood sciences laboratory is encouraged. Considerable changes in approaches to optimal use of blood components, together with the use of alternative products, have become apparent over the past decade, leading to a need to update previous guidelines and adapt them for the use of anaesthetists working throughout the hospital system.